2006
DOI: 10.1016/s1355-0306(06)71581-7
|View full text |Cite
|
Sign up to set email alerts
|

Sediment Fingerprints: A forensic technique using quartz sand grains

Abstract: The analyses of 738 soil and sediment samples taken during the investigation of 20 forensic cases are combined in a database for retrospective comparisons. Quartz sand grain surface textures are combined into grain types which are analysed at one of five orders of classification. This classification also provides frequency data on the number of grain types found in a sample, the individuality of the quartz grain type assemblages and quartz grain type ratios. The technique, developed primarily as an exclusion m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(42 citation statements)
references
References 12 publications
1
41
0
Order By: Relevance
“…Samples taken from the badger sett site proved to be predominantly quartz which were comprised of three main quartz grain textural groupings [12]. This combination of textural groupings is not found in any of the thousand sample locations found in the paper above and so can be excluded as having derived from any previously sampled source in Britain.…”
Section: Suspected Badger (Meles Meles) Baiting Identified By Comparimentioning
confidence: 75%
See 1 more Smart Citation
“…Samples taken from the badger sett site proved to be predominantly quartz which were comprised of three main quartz grain textural groupings [12]. This combination of textural groupings is not found in any of the thousand sample locations found in the paper above and so can be excluded as having derived from any previously sampled source in Britain.…”
Section: Suspected Badger (Meles Meles) Baiting Identified By Comparimentioning
confidence: 75%
“…This generally ubiquitous mineral, found in most soils, contains grain types (these are an amalgam of suites of grain surface features) that can vary dramatically from site to site. Bull and Morgan [12] identify that there are only a very discrete number of quartz grain types found in each sample, taken across England (n = c.1000 from which a database was constructed) and that it is possible to compare comparator grains to sample grains, and if the quartz grain types were different, then they could be excluded from having derived from the same source.…”
Section: The Philosophy and Nature Of Forensic Geosciencementioning
confidence: 99%
“…Furthermore, the distinctive, elongated grains observed were present at all locations. It has been demonstrated that across the UK, on average there are 2-3 distinct grain types present at a given location 42 , so the lack of diversity within these samples is distinctive, but ultimately for this study did not provide additional discriminatory information for these samples taken from different locations within the park.…”
Section: Quartz Grain Surface Texture Analysismentioning
confidence: 82%
“…Quartz grains are highly persistent and abundant in soil samples and analysis of quartz grain surface texture by SEM can be used to reconstruct the geological history of the quartz grains present in soils and sediments 41 . The technique has previously been demonstrated to be highly informative in the investigation of the provenance of geoforensic samples 18,42 and offers a number of advantages in forensic investigations since it requires very small quantities and a simple and non-destructive sample preparation, which aids the interpretation of data derived from samples comprising mixtures of material from different provenances 16 . Quartz grain surface texture analysis has been shown to work well in combination with other forensic analytical techniques in previous studies 18,25 and was, therefore, considered a good candidate for use in conjunction with HPLC.…”
Section: Introductionmentioning
confidence: 99%
“…It further enhances the ability of the experienced electron microscopist to designate the grain type after viewing 3 0-40 textures and noting their presence or absence on a grain in order that a provenance designation can be made. Of course, in the context of a forensic case this academic interpretation is not needed for a meaningful presentation of findings to the court (see our Table 2 and related discussion [1]). …”
mentioning
confidence: 99%